Sociodemographic factors, parental mental health and movement behaviours in the early years: the SUNRISE Finland Study protocol - Engberg, Elina (BioMed Central Ltd., 2026)
Background The World Health Organization (WHO) has identified the prevention of obesity in young children as one of its key priorities for the 21st century, and 24-hour movement behaviours (physical activity, sedentary behaviour and sleep) play a key role in this priority. The SUNRISE Finland Study is part of the international SUNRISE Study, which examines the movement behaviours of young children in 64 low-, middle- and high-income countries. The SUNRISE Finland Study will investigate what proportion of 3- to 4-year-old children living in Finland meet the WHO global guidelines on 24-hour movement behaviours, and how that proportion and children’s motor and cognitive skills compare with children from other countries involved in the SUNRISE Study. We also aim to identify potential correlates of children’s movement behaviours, focusing on socioeconomic factors, residential environmental features, and parents’ mental health. In addition, this study will examine the associations between children’s movement behaviours, motor and cognitive skills, adiposity, and psychosocial wellbeing. Finally, we aim to establish a cohort of families who participate in the study and conduct follow-ups in the future.
Methods We will recruit 1,000 children aged 3.0 to 4.9 years and their caregivers through early childhood education and care centres in Finland (50% in urban and 50% in rural areas). We will assess children’s 24-h movement behaviours using two accelerometers and a parental report. Children will perform validated tests to measure gross and fine motor skills and executive functions, and their height, weight and waist circumference will be measured. Caregivers will complete questionnaires regarding sociodemographic factors, nature visits, their own movement behaviours, symptoms of depression, anxiety, stress, insomnia, nomophobia, social media self-control failure, and happiness, and child’s psychosocial wellbeing. Geographic Information System (GIS) will be used to examine residential environmental features.
Discussion In addition to facilitating international comparisons on movement behaviours and motor and cognitive skills, the SUNRISE Finland Study will provide novel evidence on factors associated with movement behaviours in young children. The results of this study will help in planning actions to promote healthy levels of movement behaviours at an early age and equal opportunities for healthy development.